Effect of pre-culture on virus elimination from in vitro apple by thermotherapy coupled with shoot tip culture - Guo-jun HU; Ya-feng DONG; Zun-ping ZHANG; Xu-dong FAN; Fang REN; Zheng-nan LI (Journal of Integrative Agriculture, 2018)
We evaluated the role of pre-culture on survival rate of in vitro apple plants treated by thermotherapy. Two apple cultivars, Malus×domestica cv. Pink Lady and Huafu, were used in the experiment and both have widely grown in China and infected with Apple chlorotic leaf spot virus (ACLSV) and Apple stem grooving virus (ASGV). Results in growth and virus titer of apple plants did not exhibit clear trends during five different periods of pre-culture. Whilst, pre-culture increased the survival rate of the two cultivars during thermotherapy. The survival rate of plants pre-cultured for 13 d (P-13d) was 14 and 51% higher than that of P-1d plants for Pink Lady and Huafu, respectively. Moreover, pre-culture positively influenced regeneration of Huafu plants. The average survival rate of plants regenerated from P-1d and P-4d was 20% lower than that regenerated from P-7d, P-10d, and P-13d. The efficiency of virus eradication was determined by reverse-transcription PCR with two primer pairs for each virus, and the detection results showed that pre-culture scarcely affected apple virus elimination. Despite the fact that the two viruses were hardly detected at 5 d of thermotherapy, no virus-free plants were found in the two cultivars of regenerated apple plantlets after 30-d treatment.